Generalized empirical likelihood non-nested tests - Ramalho, J. J. S.; Smith, R. J. (Journal of Econometrics, 2002)
This paper examines non-nested tests for competing moment condition models using a semi-parametric generalized empirical likelihood (GEL) framework. The resultant GEL estimators are first order asymptotically equivalent to those based on generalized method of moments (GMM). Cox-type, moment encompassing and parametric encompassing non-nested tests for competing moment condition models are proposed. Simulation experiments are conducted to examine the efficacy of the proposed GEL statistics in terms of their size and power properties and to compare their properties with those of corresponding non-nested test statistics based on GMM estimation.